Investigation of Heavy Metals Pollution along the Nigde-Kayseri Road, Turkey - GURHAN YALCIN, M.; BATTALOGLU, RIFAT (Asian Journal of Chemistry, 2010)
The study area comprises the D765 state road connecting Nigde and Kayseri cities in the central Anatolia. The aim of this study is to determine the heavy metal contamination in off roadside soils along the D765 state road. Heavy metal concentrations were measured with Spectro-Xepos Benchtop X-Ray Fluorescence Spectrometer. Results of heavy metal analyses on soil samples reveal a significant contamination. Average heavy metal concentrations and standard deviations of samples collected from off roadside soils along the D765 state road are as follows: As: 27.90 (7.64), Cd: 3.99 (0.35), Co: 35.80 (2.19), Cr: 158.33 (46.27), Cu: 48.37 (24.73), Fe: 31516.83 (6545.26), Mn: 771.83 (121.41), Mo: 28.52 (5.51), Ni: 118.11 (27.90), Pb: 107.48 (37.90), Sn: 6.34 (1.35), Ti: 3369.87 (1172.44) Zn: 135.64 (32.42) mg/kg. In this study, among the heavy metals, As, Cd, Co, Cr, Mo, Ni and Pb are toxic metals. Heavy metal accumulations in soil were determined to be closely associated with traffic intensity.